Analisis Peningkatan Kemampuan Berpikir Kreatif Siswa Melalui Flipbook Berbasis Science, Technology, Engineering and Mathematics (STEM) pada Topik Bioplastik - Andinisa Rahmaniar; Shinta Purnamasari; Rini Sumartini (Universitas Garut, 2026)
Students' creative thinking skills remain relatively low due to teacher-centered instruction and the limited use of interactive, innovative teaching materials in science learning. This study aims to analyze improvements in students' creative thinking skills through the use of Science, Technology, Engineering, and Mathematics (STEM)-based flipbook on bioplastics. The study used a quantitative, pre-experimental design with a one-group pretest-posttest. The research sample consisted of 30 ninth-grade students from a junior high school in Garut Regency, selected purposively. The instrument used was an essay test measuring creative thinking skills across four indicators: fluency, flexibility, originality, and elaboration. Data were analyzed using the Shapiro-Wilk normality test, the Wilcoxon test, and the N-Gain test. The results showed an increase in students' creative thinking skills, indicated by an average pretest score of 39.22, which increased to 77.42 in the posttest. The Wilcoxon test showed a p-value of 0.000 (< 0.05), indicating a difference between the pre- and post-treatment groups. The N-Gain values ​​for all indicators were in the moderate category, with the highest increase in the flexibility indicator (0.69) and the lowest in elaboration (0.58). These N-Gain results indicate that STEM-based flipbooks on bioplastics can help students develop ideas, explore various solutions, and link concepts to contextual problems. This research has the potential to improve junior high school students' creative thinking skills.Keywords: bioplastics, creative thinking, flipbook, STEM